2015
DOI: 10.1007/s00705-015-2648-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings

Abstract: The circulation of duck hepatitis A virus types 1 (DHAV-1) and 3 (DHAV-3) in Southeast Asia has resulted in a continuously changing epidemiological scenario. In this study, a duplex real-time PCR assay for simultaneous quantitative detection of DHAV-1 and DHAV-3 was established, and 200 liver samples from dead ducklings collected from 31 different flocks in Shandong province, China, were tested. Fifty-eight (29.0 %) samples from 13 flocks were positive for DHAV-1 single infection, 113 (56.5 %) samples from 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…DHAV‐3 accounts for an increasing proportion of pathogens in South Korea (Cha, Roh, Kang, Kim, & Jang, ; Kim et al., ), mainland China (Liu et al., ) and Vietnam (Roan et al., ). Additionally, outbreaks with co‐infections of DHAV‐1 and DHAV‐3 have recently been reported in mainland China and South Korea (Lin et al., ; Soliman et al., ). Beginning in 2013, two officially approved live‐attenuated vaccines against DHAV‐1 strains (CH60 and A66) have been widely used to vaccinate breeder ducks in China; however, investigations into the epidemiology of DHAV infection have lacked since that time.…”
Section: Introductionmentioning
confidence: 99%
“…DHAV‐3 accounts for an increasing proportion of pathogens in South Korea (Cha, Roh, Kang, Kim, & Jang, ; Kim et al., ), mainland China (Liu et al., ) and Vietnam (Roan et al., ). Additionally, outbreaks with co‐infections of DHAV‐1 and DHAV‐3 have recently been reported in mainland China and South Korea (Lin et al., ; Soliman et al., ). Beginning in 2013, two officially approved live‐attenuated vaccines against DHAV‐1 strains (CH60 and A66) have been widely used to vaccinate breeder ducks in China; however, investigations into the epidemiology of DHAV infection have lacked since that time.…”
Section: Introductionmentioning
confidence: 99%
“…Given that DHAV-3 is most prevalent in duck industry in East and South Asia (Fu et al, 2008; Soliman et al, 2015; Doan et al, 2016; Lin et al, 2016), the resistance breeding against DHAV-3 was started in 2014 in our laboratory by using 88 families of a Pekin duck specialized line (Z8) as a tested flock (Zhang et al, 2016). As a first step toward the resistance breeding, the authors investigated the resistance and susceptibility of Pekin duck strain Z8, a lean-type line of Pekin duck, to DHAV-3 by using experimental infections.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research had revealed that duck hepatitis A virus (DHAV) type 1 (DHAV-1) and type 3 (DHAV-3) were detected with high viral loads in all the tested organs (liver, spleen, thymus, pancreas, brain, thymus, kidney and BF) of clinical infected Cherry Valley ducklings [44]. In this study, high viral loads of DAstV-1 was firstly identified in all the different tested organs (liver, spleen, kidney, thymus, BF, heart and small intestines) of the infected ducklings, indicating that DAstV-1 also had extensive tissue tropism.…”
Section: Discussionmentioning
confidence: 99%